Analisis Pola Dispersi Total Suspended Particulate (TSP) dengan Variasi Waktu dan Tempat pada Tambang Batu Kapur - Mita Fardella; Vera Surtia Bachtiar; Slamet Raharjo (Fakultas Teknik, 2023)
Mining activity is one of the producers of coarse particulates and fine particulates in the air which can have an impact on the surrounding environment. Limestone mining carried out by PT. Semen Padang is likely to contribute particulates such as Total Suspended Particulate (TSP) in the air. This study evaluates the dispersion pattern of TSP with variations in time and place to see its movement and direction of spread to determine affected areas or areas with high pollutants. Sampling and location determination refers to SNI 19-7119.6-2005 which consists of 30 observation points in 8 cardinal directions in the area around mining. Meteorological data was taken to see the dominant wind direction using the PCE-FWS 2.0 tool and then processed using the WR Plot software. TSP concentrations were measured using an EPAM 5000 tool which was divided into 4 shifts with the duration of each shift measured for 30 minutes, then TSP concentrations were mapped using Surfer 10 software. The results showed that TSP concentrations in the morning and afternoon were influenced by sampling distance and mining activity. , while the concentration of TSP at night is influenced by the wind direction and the sampling location. The TSP dispersion pattern in the morning and afternoon tends to be east, south, and west, while at night the dispersion pattern tends to be high in the southwest direction.